2004
DOI: 10.1111/j.0022-0477.2004.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tephra deposition on mire vegetation: a field experiment in Hokkaido, Japan

Abstract: Summary 1The influence of tephra (aerially transported volcanic ejecta) on mire vegetation was investigated in a field experiment at Sarobetsu Mire, northern Hokkaido, Japan, which simulated relatively thin, widespread tephras. It was carried out in the centre of a raised part of the mire in a Carex middendorffii -Sphagnum papillosum community. 2 We tested the effects of varying tephra layer thickness, grain size and season of the simulated tephra impact. 3 Vegetation surveys and analyses of the mire pore wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 35 publications
0
43
0
1
Order By: Relevance
“…Racomitrium lanuginosum can absorb falls of up to 8cm without incurring significant 108 damage; Zobel & Antos (1997) noted moss recovery from falls < 2cm in forest adjacent 109 to Mount St. Helens and Hotes et al (2004) reported the recovery of Sphagnum spp. 110 moss from beneath deposits 6cm thick.…”
mentioning
confidence: 99%
“…Racomitrium lanuginosum can absorb falls of up to 8cm without incurring significant 108 damage; Zobel & Antos (1997) noted moss recovery from falls < 2cm in forest adjacent 109 to Mount St. Helens and Hotes et al (2004) reported the recovery of Sphagnum spp. 110 moss from beneath deposits 6cm thick.…”
mentioning
confidence: 99%
“…During the terrestrialization, peat, mostly consisting of Sphagnum spp., accumulated, and the peat depth now reaches ca. 6 m (Hotes et al 2004). Two major vegetation types that must have been major components of the original vegetation are the Carex middendorffii-Sphagnum papillosum community and the Carex middendorffii-Sphagnum magellanicum community (Tachibana and Ito 1980).…”
Section: Study Areamentioning
confidence: 99%
“…Tephra deposits are generally deepest in close proximity to the volcanic vent, and become progressively thinner with increasing distance from the source (Carey 2005). The effect of tephra on vegetation is primarily related to the depth (thickness) of the ejected material (Eggler 1963;Vucetich & Pullar 1963;Hotes et al 2004;Antos & Zobel 2005;Tsuyuzaki & Hase 2005;Gomez-Romero et al 2006).…”
Section: Introductionmentioning
confidence: 99%